Belgische Kunst 1960-1970. - Gevaert, Yves (Köln : Kölnischer Kunstverein, 1970)
Arnould, Marcel ; Exell, Evelyne ; Beullens, André ; Broisson, Jean ; Broodthaers, Marcel ; Charlier, Jacques ; Chemay, Jacques ; Elias, Etienne ; Ghysels, Jean-Pierre ; Lacomblez, Jacques ; Laenen, Jean-Paul ; Lahaut, Pierre ; Leblanc, Walter ; Mestdagh, Roberte ; Panamarenko ; Persoons, Hans ; Raveel, Roger ; Roobjee ; Roquet, Maurice ; Szukalshy, Albert ; Van den Abbeel, Jan ; Van den Branden, Guy ; Vandercam, Serge ; Van Hoeydonck, Paul ; Verheyen, Jef ; Verstockt, Marc
Belgische Kunst 1960-1970, Kölnischer Kunstverein, Köln, 4. September bis 4. Oktober 1970
boek
Keywords: België